2008
DOI: 10.1016/j.jcrs.2008.08.038
|View full text |Cite
|
Sign up to set email alerts
|

In vitro femtosecond laser-assisted nanosurgery of porcine posterior capsule

Abstract: Nonamplified near-infrared femtosecond laser pulses at low pulse energies may be a promising strategy for precise lamellar noncontact nanosurgery of the posterior capsule, with minimal structural collateral damage to surrounding tissue. High-resolution MLSM offers 3-dimensional, noninvasive, nondestructive imaging at submicrometer resolution within seconds before and after ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Laser-assisted cataract surgery (LACS) uses ultrashort pulse lasers to precisely photodisrupt the crystalline lens [24][25][26]. Several authors have reported reduction of PHACO time and energy as well as reduction of EC loss among animal and human eyes undergoing laser lens fragmentation (LLF) [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Laser-assisted cataract surgery (LACS) uses ultrashort pulse lasers to precisely photodisrupt the crystalline lens [24][25][26]. Several authors have reported reduction of PHACO time and energy as well as reduction of EC loss among animal and human eyes undergoing laser lens fragmentation (LLF) [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The FS laser allows improved incision precision, thus limiting destruction of surrounding normal tissue. 6,7 Creation of leak-free clear corneal incisions (CCI) to improve wound healing postsurgery is an important step toward reducing/eliminating postsurgery complications.…”
mentioning
confidence: 99%